Mujeres del Río Chubut : aprendizajes alrededor del agua - Raguileo, Daniela Ayelen; Pessacg, Natalia; Guiñazu, María Mercedes; Liberoff, Ana Laura (EEA Chubut, INTA, 2022)
Presentación del trabajo en el minuto 22 del seminario: https://www.youtube.com/watch?v=8zqZuPYwhgk